(untitled) (Research, Society and Development, 2023)
The present study is of great importance, as it deals with a relevant topic in the lives of many families, portraying a particularity whose, specifically the impact of ASD on the lives of children and family members, through research, was possible to point out strategies that can help in the progressive evolution of the child with ASD, as well as, through the implementation of nursing care. Objective: To understand the importance of investigating and treating factors that involve the quality of life of family members and children with ASD. Materials and methods: This is a literature review. Eight scientific articles were analyzed, being published between the years 2018 to 2022. Having as database: collection+, uniCEUB, online ID. Journal of psychology, Revista Saúde e Desenvolvimento, unifametro, core of knowledge, through terms of the Descriptors in Health Sciences (DeCS): Child, Nursing care, Nurse, Autistic Spectrum Disorder. Results: The study provided the identification of positive and negative actions through monitoring the family member and the child. Final considerations: The study made it possible to understand that the nurse and the family can be the main protagonists of the quality of life of children with ASD.